2010
DOI: 10.1038/leu.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

The t(6;9) associated DEK/CAN fusion protein targets a population of long-term repopulating hematopoietic stem cells for leukemogenic transformation

Abstract: The t(6;9)-positive acute myeloid leukemia (AML) is classified as a separate clinical entity because of its early onset and poor prognosis. The hallmark of t(6;9) AML is the expression of the DEK/CAN fusion protein. The leukemogenic potential of DEK/ CAN has been called into question, because it was shown to be unable to block the differentiation of hematopoietic progenitors. We found that DEK/CAN initiated leukemia from a small subpopulation within the hematopoietic stem cell (HSC) population expressing a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 26 publications
4
56
0
7
Order By: Relevance
“…This is not surprising considering the fact that LSAs are formed by genetic alterations (chromosomal translocations or gene mutations) that are causally involved in leukemogenesis. [50][51][52][53][54] Several LAAs have also been implicated in the multi-step leukemic transformation of hematopoietic progenitor cells, for example, ETO/MTG8, 55 hTERT 56 and the homeobox protein HOXA9. 57 The LAA WT1 may contribute to leukemogenesis by interfering with normal hematopoietic progenitor cell differentiation, which is considered as one of the first critical steps in the leukemic transformation of these cells.…”
Section: Leukemogenesismentioning
confidence: 99%
“…This is not surprising considering the fact that LSAs are formed by genetic alterations (chromosomal translocations or gene mutations) that are causally involved in leukemogenesis. [50][51][52][53][54] Several LAAs have also been implicated in the multi-step leukemic transformation of hematopoietic progenitor cells, for example, ETO/MTG8, 55 hTERT 56 and the homeobox protein HOXA9. 57 The LAA WT1 may contribute to leukemogenesis by interfering with normal hematopoietic progenitor cell differentiation, which is considered as one of the first critical steps in the leukemic transformation of these cells.…”
Section: Leukemogenesismentioning
confidence: 99%
“…Oancea et al reported that Dek is responsible, in part, for the leukemogenic transformation of hematopoietic stem cells. 155 A rare but clinically severe type of acute myeloid leukemia is caused by the t(6;9) chromosomal translocation that creates a fusion gene between DEK and the CAN nuclear pore complex protein. 156 This finding led to the original discovery of DEK, and the fusion protein maintains all but the C-terminal region of the DEK oncogene and is under control of the DEK promoter.…”
Section: Dek Regulates Chromatin Structure and Function In Normal Andmentioning
confidence: 99%
“…15,16 The leukemogenic potential of the fusion protein is restricted to a very small subpopulation of hematopoietic stem cells. 17 The characteristics of t(6;9)/DEK-NUP214 AML have so far not been separately described in pediatric patients and the prognostic impact in pediatric AML is unclear. 1,12,13,18 The aims of this study were to characterize the clinical, genetic and morphological features of t(6;9)-positive childhood myeloid neoplasms in the largest series so far; to evaluate outcome and to identify genes potentially involved in leukemogenesis of t(6;9) using gene expression profiling.…”
Section: Introductionmentioning
confidence: 99%